Loss of miR-369 Promotes Tau Phosphorylation by Targeting the Fyn and Serine/Threonine-Protein Kinase 2 Signaling Pathways in Alzheimer’s Disease Mice - Yao, Xiaoguang; Xian, Xiaohui; Fang, Mingxing; Fan, Shujuan; Li, Wenbin (Frontiers in Aging Neuroscience, 2020)
Introduction Alzheimer’s disease (AD) is a progressive neurodegenerative dementia with the key pathological hallmarks amyloid-beta deposition and neurofibrillary tangles composed of hyperphosphorylated tau. microRNAs (miRNAs) are small non-coding RNAs that contribute to the pathogenesis of AD. In this study, we investigated the effect of the loss of miR-369 on the phosphorylation of tau protein and the activation of the kinases Fyn and serine/threonine-protein kinase 2 (SRPK2) as the upstream molecules facilitating tau phosphorylation in miR-369 knockout 3xTg-AD mice. Methods We generated miR-369 knockout 3xTg-AD mice and investigated their cognitive behaviors by maze tests. Real-time qPCR, western blot, and immunohistochemistry were performed to evaluate the expression of the miR-369 gene, phosphorylation of tau protein, and activation of Fyn and SRPK2. Luciferase reporter assays were applied to confirm the predicted targets of miR-369. Results Knocking out miR-369 in 3xTg AD mice aggravated cognitive impairment, promoted hyperphosphorylation of tau, and upregulated Fyn and SRPK2. Restoring miR-369 reversed the hyperphosphorylation of tau and downregulated Fyn and SRPK2. Additionally, miR-369 was shown to target the 3′UTRs of Fyn and SRPK2 to regulate their expression levels. Conclusion Loss of miR-369 promotes tau phosphorylation by targeting the Fyn and SRPK2 signaling pathways in AD mice, and supplementation with miR-369 might be a valuable option for AD therapeutic studies.